Image processing algorithms for coronary blood flow estimation - Ma, Jun Jie (2008)
This project reviews and implements using C Programming Language two image processing algorithms proposed by Wang [9], the two-dimensional Cross Correlation (CC) algorithms and the Constraint Line Clustering (CLC) algorithm, for estimating coronary blood flow velocity from x-ray coneagiogram image sequence.